Dukungan Keluarga terhadap Kualitas Hidup Pasien Kanker Serviks - Purwaningsih, Heni; Oktaviani, Ulva (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Cervical Cancer is the disease with the most suffered by people after Breast Cancer. Cancer cause decrease ofcondition in both physical and psychological. The impact of this cervical cancer makes sufferers needfamily support. The purpose of this study determined the correlation between family support and the lifequality of cervical cancer patients in Dr. Moewardi Surakarta. This study used a quantitative method with adescriptive approach. The samples in this study were 88 samples. The research instrument used the EORTCQLQ C30 Life Quality questionnaire, and data were analyzed by using Chi Square test. The results showedobtain respondents who get less family support, most of their quality of life is lack as many as 8 respondents(47.1%). Respondents with sufficient family support, mostly have poor life quality as many as 18respondents (58.1%). While respondents who receive good family support, mostly have good life quality asmany as 22 respondents (55.0%). Chi Square test results obtain p-value 0,000 <α (0,05), so that it can beconcluded that there is significant correlation between family support and the life quality of Cervical cancerpatients in Dr. RSUD. Moewardi Surakarta. Some suggestions for the family are; people should provide moremotivation, support and more attention to the condition of cervical cancer patients. Meanwhile, for the healthworkers, they should concern more in supporting patients in order to improve the life quality for patients withCervical Cancer.